The effect of collaborative mobile augmented reality application on students learning performance (IR) - Hafizul Fahri Hanafi (2017)
The objective of this study is to develop and test the effect of a mobile learning application, called Collaborative Mobile Augmented Reality Learning Application (CoMARLA), on student learning achievement and motivation in learning the Information Technology course. The development of CoMARLA is based on a framework guided by Moshmans constructivist learning principles and Kellers motivation principles. This study was based on a quantitative approach using a quasiexperimental method that employed a 2 by 2 factorial research design. The independent variable was the learning method and the dependant variables were students learning achievement and motivation, with gender as the moderator variable. The sample of the study consisted of 120 social science undergraduates, with a mean age of 19.5 years, who were divided into an experimental and a control group. The experimental group received treatment with the use of CoMARLA on the mobile platform, while the control group received the same treatment with the use of similar application on the desktop platform. The research instruments used were a set of multiple-choice test and Intrinsic Motivation Inventory to measure students learning achievements and motivation, respectively. A series of tests based on the independence t-test and Analysis of Covariance (ANCOVA) were performed on the data. The findings showed the students learning achievements and motivation after treatment were significantly higher than they were before treatment. The same findings showed the experimental groups learning achievement and motivation after treatment were significantly higher than those of the control group. In addition, male participants learning achievement was significantly higher than that of female participants. However, no significant difference in motivation between the two genders was observed. Overall, the findings suggest that such a novel mobile learning application can be used to help improve the learning achievement and motivation of social science undergraduates in learning Information Technology course.